English Language Testing in Moodle: Step Towards University of Latvia Language Policy Implementation - Indra Karapetjana; Jana Kuzmina; Zigrīda Vinčela (Baltic Journal of English Language, Literature and Culture, 2016)
Along with globalisation, university internalisation has taken place, leading to the support for the national and foreign language policies in universities. This has resulted in the expansion of English as a lingua franca of academia. The aims of this study were to discuss the results of the focused descriptive study aimed at obtaining information on the status quo of the students’ English language proficiency level at the University of Latvia (UL) and the feasibility of the introduction of an in-house Moodle-based testing introduction into the learning process at the UL. The piloted test results demonstrate that generally the students have an appropriate English language proficiency level for academic studies at the UL at all degree levels, although exhibiting limitations in writing and some limitations in listening skills. It has also been concluded that Moodle-based online language testing is helpful to meet the language policy goals set out at the University of Latvia.